U-Pb zircon ages for the porphyritic microgranite of the Shewa-Shahbazgarhi Complex, district Mardan, North Pakistan - Ahmad, Irshad; Danishwar, Shuhab Khan; Lapen, Tom; Jehan, Noor (Journal of Himalayan Earth Sciences, 2013)
The Shewa-Shahbazgarhi complex is an isolated triangular outcrop, occurring about 12 km northeast of Mardan and resides 60 km south of the Main Mantle thrust (MMT) as part of the Indian plate. It comprises of basic and acidic alkaline rocks including microporphry, metagabbro, metadolerite, reibeckite gneiss and porphyritic microgranite. A sample from the porphyritic microgranite yields 280 + 16 Ma year U-Pb age on zircon. Similar ages from the Swat granites (granite gneiss) and Chakdara granite gneiss including the present date show that Peshawar plain alkaline igneous province (PPAIP) rift-related igneous activity of the granitic rocks was Permian in age.